HIERARCHICAL LEVEL OF MANAGERS ABILITIES A Moderator between Quality Management Practices and Company Financial Performance - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
This study investigates the moderating impacts of hierarchical level of managers abilities on the form and strength of all structural relationships between quality management practices and company financial performance. This study describes the structural relationships among the research constructs six critical factors of quality management practices (quality improvement program, supervisory leadership, supplier involvement, management commitment, training to improve products/services, cross-functional relationships)